The relationship between menarche and nutritional status in Junior High School students in Aceh Besar. A study from 30 years of armed conflict area, Aceh, Indonesia - Muhammad Yani; Azhari Azhari; Agus Hendra Al Rahmad; Farid Bastian; Teuku Muhammad Ilzana; Cut Rizka Rahmi; Andriaty, S. Nora; Adithia Chanda; Syahnaz Salsabila (AcTion: Aceh Nutrition Journal, 2023)
Age at menarche is strongly associated with adolescents' nutritional status. Food insecurity is one of the factors that cause nutritional disorders. Communities living in areas of armed conflict often experience food insecurity and low levels of parental knowledge, leading to being underweight and stunting. Aceh had been plagued by armed conflict for almost three decades, which ended 23 years ago. This study aimed to measure the relationship between menarche and the nutritional status of adolescents in Aceh Besar, Aceh Province. This analytical research method used a cross-sectional survey approach. The sample consisted of 278 Junior High School (JHS) students, taken by stratified random sampling at ten of the JHS in Aceh Besar in 2021-2022. Data were collected through interviews, using questionnaires, anthropometric measurements (Weight and Height), and observations. Statistical analysis used the Chi-square test at CI 95%. 79,1% of the students' menarche was normal, and 64,7% had normal nutritional status. There was a significant relationship between age at menarche and nutritional status (p<0,05). In conclusion, menarche's age is related to adolescent girls' nutritional status at Junior High School in Aceh Besar.